Kegiatan Pengabdian Masyarakat dalam Rangka Edukasi Masyarakat mengenai Hiperlipidemia serta Deteksi Dini Hiperlipidemia dan Kaitannya dengan Kejadian Obesitas - Robert Kosasih; Alexander Halim Santoso; Dean Ascha Wijaya; Fernando Nathaniel; Joshua Kurniawan; Hans Sugiarto; Margaretha Pramesthi Utari; Ribka Anggelline Hariesti Sitorus; Melkior Michael Fransisco (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2023)
Hyperlipidemia is a metabolic disorder that indicates an increase in lipid levels in the body. Obesity, particularly central obesity, is correlated with hyperlipidemia and metabolic syndrome. Complications of hyperlipidemia such as coronary artery disease, type 2 diabetes, and high blood pressure can be fatal if left untreated. Education and early detection of hyperlipidemia are crucial to prevent serious complications and maintain good health. This community service involved 50 elderly at Santa Anna Elderly Care Facility. All respondents participated in a series of activities, including education through posters, physical examinations, and diagnostic tests. Results of the diagnostic tests indicated 2 respondents had LDL levels ? 135 mg/dL, 6 respondents had HDL levels < 40 mg/dL, and 12 respondents had total cholesterol levels ? 200 mg/dL. The results of the education activities are expected to increase public awareness, all of which can reduce the overall healthcare burden when applied correctly and properly.